1998
DOI: 10.2134/agronj1998.00021962009000020016x
|View full text |Cite
|
Sign up to set email alerts
|

A High Oil Pollinator Enhancement of Kernel Oil and Effects on Grain Yields of Maize Hybrids

Abstract: Several attempts to develop high oil (HO) maize (Zea mays L.) hybrids that are competitive in yield have met with limited success, because of the negative association between oil levels and grain yields. Generally, HO hybrids have high oil kernels but with reduced starch levels, smaller endosperm, and reduced kernel size. The objective of the study was to determine if the use of a high oil maize pollinator could reduce the potential grain yield losses associated with high oil maize production. Nine different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 15 publications
6
37
1
4
Order By: Relevance
“…Significant positive correlation between tryptophan and oil content was also found in Ignjatovic-Micic et al (2015). Lambert et al (1998) attributed increased lysine content in TC Blends to the larger embryo associated with high oil maize, as most essential amino acids are located in the kernel embryo. Significant increase in the germ size was noted only in TC-2 and TC-3, but their tryptophan content was at the level of the ZP341 selfed.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Significant positive correlation between tryptophan and oil content was also found in Ignjatovic-Micic et al (2015). Lambert et al (1998) attributed increased lysine content in TC Blends to the larger embryo associated with high oil maize, as most essential amino acids are located in the kernel embryo. Significant increase in the germ size was noted only in TC-2 and TC-3, but their tryptophan content was at the level of the ZP341 selfed.…”
Section: Discussionmentioning
confidence: 79%
“…Protein content was significantly lower in all TCs. On the contrary, Cromwell (2000) found that high oil maize contains up to 10 g kg −1 more protein than standard maize, while in some other research studies protein levels were similar for TC Blends and check hybrids (Lambert et al, 1998;Strachan and Kaplan, 2001;Thomison et al, 2003). The deviations from the expected results could indicate the complexity of trait inheritance.…”
Section: Discussionmentioning
confidence: 95%
“…Destacaram-se os híbridos DKB 350, A 2555, Fort, BRS 1001, CD 306, Strike, AG 7000, 30F90, Brava, BRS 1010 e 30F98 com maiores teores de óleo, os quais podem ser indicados preferencialmente para reduzir o custo energético das rações, pois é provável que, nesta faixa relativamente baixa de óleo, o teor de amido permaneça inalterado nos grãos (ALEXANDER e LAMBERT, 1968;LAMBERT et al, 1998 A massa de cem grãos apresentou correlação negativa com o teor de óleo apenas na análise conjunta, onde há influência tanto do ambiente como das cultivares, e positiva com peso volumétrico em Assis e na análise conjunta, todos com baixos índices de correlação. Logo, considerando que o germe e o endosperma possuem diferentes densidades, sendo o primeiro mais denso, espera-se que a proporção entre as frações germe e endosperma tenha variado muito pouco entre os grãos com diferentes teores de óleo.…”
Section: E Duarte Et Al (2007)unclassified
“…Geralmente, existe uma relação estreita entre os teores de óleo da fração germe e o do próprio grão porque 81% a 87% do óleo do grão está no germe (EARLE et al, 1946). Redução do tamanho e massa dos grãos com o aumento de óleo, e redução dos teores de amido, têm sido observados apenas em programas de melhoramento que atingem teores de óleo maiores que 7 % (MILLER et al, 1981;LAMBERT et al, 1998). Isso tem sido atribuído à menor eficiência metabólica na transformação de açúcar em óleo do que em amido (MILLER et al, 1981).…”
Section: E Duarte Et Al (2007)unclassified
“…This procedure consists in sowing a mixture of seeds of a normal kernel oil content high-yielding male-sterile singlecross (&90%) and a high-oil (but low-yielding) male pollinator (&10%). Lambert et al (1998) reported that hybrids pollinated with high oil and normal oil content strains had comparable yield, but those hybrids pollinated with high oil strains yielded 19 g kg -1 more oil than those pollinated with the normal oil content strains. Also, Thomison et al (2003) reported that with the Top Cross TM procedure the kernel oil content was quite higher (72.12 g kg -1 ) than in the normal single-crosses crop (41.25 g kg -1 ), but a significant reduction on grain yield was reported (Thomison et al 2002).…”
Section: Implications For Selectionmentioning
confidence: 99%